Prevalence and influencing factors of post-traumatic stress disorder among Chinese healthcare workers during the COVID-19 epidemic: a systematic review and meta-analysis - Zhang, Min; Bo, Mingyu; Wang, Huixin; Fan, Wenyi; Kong, Lingling; Zhou, Chunjie; Zhang, Zhenxing (Frontiers in Psychiatry, 2024)
Background Post-traumatic stress disorder is an important psychological problem affecting the physical and mental health of Chinese healthcare workers during the COVID-19 pandemic. Aims To estimate the prevalence and influencing factors of post-traumatic stress disorder (PTSD) among Chinese healthcare workers during COVID-19. Methods Search of Chinese and English literature in PubMed, EMbase, Web of Science, Medline, Elsevier, SpringerLink, China Biomedical Literature Database, CNKI, Wan-fang, and CQVIP for the period from December 2019 to August 2023. Stata 14.0 software was used for data analysis.The methodological quality of each study was scored, and data were extracted from the published reports. Pooled prevalence was estimated using the Random-effects model. Publication bias was evaluated using Egger’s test and Begg’s test. Results Twenty-one studies included 11841 Chinese healthcare workers in this review.First, the overall prevalence of Post-traumatic stress disorder among Chinese healthcare workers during the COVID-19 epidemic was 29.2% (95% CI: 20.7% to 33.7% ). Twelve factors included in the meta-analysis were found to be protective against PTSD among Chinese healthcare workers: female, nurse, married, front-line work, less work experience, family or friend diagnosed with COVID-19, history of chronic disease and fear of COVID-19. Conversely, outside Hubei, higher education, social support and psychological resilience are protective factors. Conclusion These recent findings increase our understanding of the psychological status of Chinese healthcare workers and encourage that long-term monitoring and long-term interventions should be implemented to improve the mental health of Chinese healthcare workers in the aftermath of the COVID-19.